Basketry and Festival Among the Dong (Kam) People - Jackson Jason Baird; Zhang Lijun (Journal of Ethnology and Folkloristics)
While fundamental to the practical concerns of everyday life, bamboo baskets also play important roles within festivals staged by the Dong (Kam) people of Southwest China. Drawing upon fieldwork in Sanjiang Dong Autonomous County in the Guangxi Zhuang Autonomous Region and in adjacent Liping County, Guizhou Province, this article will evoke and contextualize some of the ways that bamboo baskets are bought and sold, used and put on display within festivals held in this mountainous corner of China and the Southeast Asian Massif.